2000
DOI: 10.1292/jvms.62.49
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Apolipoprotein C-III Concentration in the High-Density Lipoprotein Fraction from Calves Inoculated with Pasteurella haemolytica and Bovine Herpes Virus-1

Abstract: ABSTRACT. Lipoprotein lipid and apoprotein concentrations are known to be altered during the acute-phase response. We have previously shown that the serum activity of lecithin:cholesterol acyltransferase (LCAT) and concentration of cholesteryl esters, both constituents of the high-density lipoprotein (HDL) fraction, are reduced in calves inoculated with Pasteurella haemolytica and bovine herpes virus-1, the two major pathogens for calf pneumonia. The concentration of apolipoprotein C-III (apoC-III), a low mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
3
10
0
Order By: Relevance
“…The significantly lower levels of PON-1 and HDL and the higher level of VLDL in calves affected by inflammatory conditions confirms that also in calves HDL decreases early during inflammation, as previously suggested (Yamamoto et al, 2000) and in agreement with what reported in other species (Carpentier and Scruel, 2002;Khovidhunkit et al, 2004). This decrease may be detected using both the methods employed in this study for measuring HDLs.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…The significantly lower levels of PON-1 and HDL and the higher level of VLDL in calves affected by inflammatory conditions confirms that also in calves HDL decreases early during inflammation, as previously suggested (Yamamoto et al, 2000) and in agreement with what reported in other species (Carpentier and Scruel, 2002;Khovidhunkit et al, 2004). This decrease may be detected using both the methods employed in this study for measuring HDLs.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…The value during midlactation is comparable to the reported concentration in humans [68,99,133]. ApoC-III concentrations in 2-to 3-month-old male Holstein calves [188] and Japanese black calves [193] were in the range of 20 to 40 µg/ml and were lower than those in Holstein dairy cows. The apoC-III concentration was decreased in Holstein calves with pneumonia [188], whereas greatly increased in a Japanese black calf with hyperlipidemia [193].…”
Section: Apolipoproteinssupporting
confidence: 82%
“…Except for the calf with hyperlipidemia (higher concentration in the CM than HDL fraction) [193], the predominant distribution in HDL does not change in pathologic states such as calf pneumonia [188] and cow ketosis and milk fever [192]. The low apoC-III concentration in CM appears to be due to the indistinct alimentary lipemia [144].…”
Section: Apolipoproteinsmentioning
confidence: 99%
“…The total plasma apoC-III concentration increases in hypertriglyceridemia [4], suggesting the involvement of apoC-III in the regulation of TG metabolism. By comparison, except for a calf with hyperlipidemia [23], most apoC-III in normolipidemic cattle is detected in HDL [5,19,20,22]. The redistribution by feeding from HDL to the CM and VLDL fractions is not observed [20].…”
Section: Discussionmentioning
confidence: 99%